Bone Marrow-derived Mesenchymal Stem Cells for the Treatment of Knee Osteoarthritis - Tawonsawatruk, MD, PhD, Tulyapruek; Promsang, MD, Trai; Tangchiphisut, MD, Paween; Yuktanandana, MD, Pongsak (Journal of Southeast Asian Orthopaedics, 2022)
Forty percent of people over 70 years of age suffer from knee osteoarthritis. Stem cell based therapy is one of a number of promising strategies for osteoarthritis treatment. Mesenchymal stromal /stem cells (MSCs) derived from the bone marrow are the most commonly described source of MSCs and have been widely used to promote tissue regeneration in orthopaedic conditions, particularly in osteoarthritis. A fundamental knowledge of stem cells is very important prior to translating this technology into clinical practice. Although the mechanism of MSC therapy is still uncertain, several studies have reported on the safety and outcome of using bone marrow-derived MSCs for treating osteoarthritis. However, we still cannot conclude that MSCs can regenerate long lasting cartilage tissue. The long term clinical studies need to be evaluated in the future.